How can we contribute to solving the sustainability puzzle with bioclimatic architecture? - Maria Coral Albelda-Estellés Ness (Anuari d’Arquitectura i Societat)
Bioclimatic architecture enables a symbiotic relationship between people, nature and our built environment. By focusing on the integration of freely available natural forces and materials, it promotes energy and resource efficiency, in addition to comfort. We need to make our buildings more independent from active systems, to become more sustainable. Also, we need to consider their thermal safety in case of extreme climatic events or power outages. At last, we should not only aim for thermal comfort, but thermal delight, allowing for a more varied thermal landscaping in our buildings, to allow us to engage with our environment and awaken our senses.